A língua de saturno : melancolia em Albertine Disparue, de M. Proust - Corrêa, Éder (2015)
This dissertation aims to extend the concept proposed by Marie-Claude Lambotte in which melancholy holds its own discourse, an ideia presented in Le discours mélancolique (1999), and it attempts to apply this concept in literature. The objective is to find and highlight the elements of melancholy in the literary language, in this case, using as analysis corpus the work The Fugitive by Marcel Proust. Productions in first person discourses, as in the case of the narrative studied in this research, emphasize the evaluation of the forms and the manners of manifestation of emotions in literature. The objective is to investigate the existence of a fictional discourse noticeably dominated by emotional elements, focusing on the statements and on the narrative sequences in order to reveal their own character in the manifestation of the melancholic narrator, in a language of melancholy, and in a melancholy aesthetics by Marcel Proust. Within the framework of the theory of literature, philosophy and anthropology, the focus is to build an necessary interface, in contemporaneity, to study this emotion in a work of literature.